2022
DOI: 10.1029/2022wr032299
|View full text |Cite
|
Sign up to set email alerts
|

Graph Convolutional Recurrent Neural Networks for Water Demand Forecasting

Abstract: Forecasting of urban water demand is essential today for managing water supply systems (WSSs). A reliable knowledge of the future water demand supports taking informed operational, tactical and strategical decisions. However, the stochastic nature of water demand makes the development of a robust forecasting model a challenging task (House-Peters & Chang, 2011). In the past years, machine learning methods gained considerable attention in the forecasting field, due to the increasing availability of computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…A WDS can be represented by a graph considering the nodes as the vertices and the edges as the pipes. The weights of the edges can be the flow rates, head losses, or roughness of the pipes [32,33].…”
Section: Graph Theory and Shortest Pathmentioning
confidence: 99%
“…A WDS can be represented by a graph considering the nodes as the vertices and the edges as the pipes. The weights of the edges can be the flow rates, head losses, or roughness of the pipes [32,33].…”
Section: Graph Theory and Shortest Pathmentioning
confidence: 99%
“…Wang et al [26] identified complex relationships between various meteorological factors at different sites and dissolved oxygen (DO) concentration levels, demonstrating that the integration of graph-based learning and time transformers in environmental modeling is a promising direction for future research. Zanfei et al [27] developed a novel graph convolutional recurrent neural network (GCRNN) to analyze the spatial and temporal dependencies among different water-demand time series within the same geographical area. Wang et al [28] presented an LSTM model integrating spatiotemporal attention, focusing on more valuable time and spatial features, to predict water levels in the middle and lower reaches of the Han River.…”
Section: Introductionmentioning
confidence: 99%
“…Water demand modeling is key for better managing the water resource. In fact, adopting datadriven algorithms that can learn from the demand data is the basis for many applications that are fundamental for the proper water management [13]. For instance, developing a short-term model able to accurately predict the following hours of demand can help for the anomaly detection task [14].…”
Section: Introductionmentioning
confidence: 99%